Transcriptomic Landscape of Colorectal Mucinous Adenocarcinoma has Similarity with Intestinal Goblet Cell Differentiation - Liu, Jianbo; Qiu, Siyuan; Fu, Xiaorui; Zhou, Bin; Zu, Ruijuan; Lv, Zhaoying; Li, Yuan; Yang, Lie; Zhou, Zongguang (Current genomics, 2025)
Introduction: Colorectal mucinous adenocarcinoma (MC) differs from adenocarcinoma (AD) in clinical features and molecular characteristics. The current treatment of colorectal MC is not precise enough, and the molecular characteristics remain unclear. The study aims to explore the difference between colorectal MC and AD on the transcriptome level for the possibility of treating colorectal MC precisely. Methods: The data of colorectal cancer (CRC) patients from The Cancer Genome Atlas (TCGA) database was assessed, and then differential analysis and weighted gene co-expression network analysis (WGCNA) were performed to identify the differential hub RNAs between colorectal MC and AD. Differential hub lncRNAs and hub RNA of significant modules were validated by quantitative real-time PCR (qRT-PCR) among different colon cancer cell lines. Results: In total, 1680 differential expressed RNAs (DERs) were found by comparing colorectal MC (52, 13.3%) with AD (340, 86.7%). Through the WGCNA, a mucin-associated RNA module was identified, while some others might be associated with unique immune progress. Finally, 6 differential hub RNAs in the mucin-associated RNA module (CTD-2589M5.4, RP11-234B24.2, RP11-25K19.1 and COLCA1) were validated by qRT-PCR and showed higher expression levels in mucin-producing colorectal cell lines (Ls174T and HT-29). Conclusion: This study suggests that clinical treatments for colorectal MC should be differentiated from AD. Further exploration of enterocyte (goblet cell) differentiation with tumor genesis and the distinct immune progression of MC may help to identify key therapeutic targets for colorectal MC. Further research on the application of immunotherapy to colorectal MC is needed.